Expression and Functional Analyses of Nymphaea caerulea MADS-Box Genes Contribute to Clarify the Complex Flower Patterning of Water Lilies - Moschin, Silvia; Nigris, Sebastiano; Ezquer, Ignacio; Masiero, Simona; Cagnin, Stefano; Cortese, Enrico; Colombo, Lucia; Casadoro, Giorgio; Baldan, Barbara (Frontiers in Plant Science, 2021)
Nymphaeaceae are early diverging angiosperms with large flowers characterized by showy petals and stamens not clearly whorled but presenting a gradual morphological transition from the outer elements to the inner stamens. Such flower structure makes these plant species relevant for studying flower evolution. MADS-domain transcription factors are crucial components of the molecular network that controls flower development. We therefore isolated and characterized MADS-box genes from the water lily Nymphaea caerulea. RNA-seq experiments on floral buds have been performed to obtain the transcript sequences of floral organ identity MADS-box genes. Maximum Likelihood phylogenetic analyses confirmed their belonging to specific MADS-box gene subfamilies. Their expression was quantified by RT-qPCR in all floral organs at two stages of development. Protein interactions among these transcription factors were investigated by yeast-two-hybrid assays. We found especially interesting the involvement of two different AGAMOUS-like genes (NycAG1 and NycAG2) in the water lily floral components. They were therefore functionally characterized by complementing Arabidopsis ag and shp1 shp2 mutants. The expression analysis of MADS-box genes across flower development in Nymphaea caerulea described a complex scenario made of numerous genes in numerous floral components. Their expression profiles in some cases were in line with what was expected from the ABC model of flower development and its extensions, while in other cases presented new and interesting gene expression patterns, as for instance the involvement of NycAGL6 and NycFL. Although sharing a high level of sequence similarity, the two AGAMOUS-like genes NycAG1 and NycAG2 could have undergone a subfunctionalization or a neofunctionalization, as only one of them could partially restore the euAG function in Arabidopsis ag-3 mutants. The hereby illustrated Nymphaea caerulea MADS-box gene expression pattern might mirror the morphological transition from the outer to the inner floral organs, and the presence of transition organs such as the petaloid stamens. This study is intended to broaden knowledge on the role and evolution of floral organ identity genes and the genetic mechanisms causing biodiversity in angiosperm flowers.